TMOD-21. TARGETING ANAPLASTIC MENINGIOMA WITH PANOBINOSTAT IN PATIENT-DERIVED ORTHOTOPIC XENOGRAFT (PDOX) MODELS DERIVED FROM A MATCHING PAIR OF PRIMARY AND RECURRENT TUMORS. (11th November 2019) - Zhang, Huiyuan; Qi, Lin; Du, Yuchen; Braun, Frank; Kogiso, Mari; Huang, Lei; Klisch, Tiemo; Zhao, Yanling; Guo, Lei; Li, Can; Zhao, Sibo; Lindsay, Holly B; et al.
Abstract: BACKGROUND: Meningioma is the most common brain tumor in adults. Despite the overall benign nature of meningioma, skull base tumors can be difficult to completely resect while others exhibit progression and aggressive profiles. The lack of clinically relevant animal models is blocking the development of novel therapies. MATERIAL AND METHODS: Twelve surgical specimens (1 × 10 5 ) from 11 adult meningioma patients were implanted into the frontal cranial-base of the brain of SCID mice. Mice were then followed and assessed for tumor formation. Tumor growth was confirmed by small animal MRI. Pathologic features of the PDOX models and the matched patient tumors were compared with standard H&E and immunohistochemical staining. RNAseq was performed to examine the molecular fidelity of PDOX tumors and to identify new therapeutic targets. A panel of 60 clinically-relevant drugs was developed for screening drug sensitivity. In vivo examination of therapeutic efficacy of Panobinostat was performed in two models by treating preformed PDOX tumors with i.p. injection (10 mg/kg), 5 days on, 5 days off for 2 cycles. RESULTS: Intracranial xenograft formation was confirmed in two samples derived from the same patient, the first an atypical meningioma (K029MEN-P) and the second, which progressed to anaplastic meningioma at recurrence (K029MEN-R). MRI scanning revealed that the PDOX tumors grew from the skull base. These patient tumor cells can be cryopreserved for long-term maintenance of tumorigenicity. The xenograft tumors replicated histopathological features of parental tumors. Overall gene expression profiles of PDOX were similar to the original patient tumors. Using MEN primary culture cells, we screened 60 drugs and identified 12 (20%) active compounds. Panobinostat also significantly prolonged survival of mice bearing orthotopic meningiomas. CONCLUSION: A set of meningioma PDOX models derived from primary and recurrent tumor was established. Our data further demonstrate that panobinostat exerts potent antitumor activity against high-grade meningioma.